Cultural dimensions among Malaysian employees - Zawawi, Dahlia (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This study explores the similarities and differences of cultural values among the Malay, Chinese, and Indian management employees in Malaysia, mainly via a case study of Nestlé in Malaysia, one of the major multinational organisations in the country. Qualitative approach was taken where 13 management employees were interviewed. This study shows several new patterns of cultural values emerging among the employees of Nestlé in Malaysia. Primarily, it extends the literature, by providing further understanding on the issues of cultural values on the Malaysian society.